Simulated Identity and Virtual Self—The Madonna-image and the Popular Icon - Gyuris, Norbert (FOCUS: Papers in English Literary and Cultural Studies, 2024)
By the end of the 20th century, the production of popular music had reached an ecstatic stage of its development. It had never been more dependent on the commercial interests of all the parties involved in the making and consumption of the available music scores, and this considerably changed those strategies that the musical icon, the popular “star,” now had to follow to keep up with ever growing competition in order to make a profit and follow a professional and long-term career. In the 1960s and early 70s, the United States and Great Britain saw the rise of an abundance of popmusic bands, some of them now famous for only one song (Steppenwolf), some of them starting a long-lasting musical career (The Beatles, The Who). The promotion of these popular icons was mainly dependent on the direct form of the frontal, but distanced mega-concerts, while the 1980s introduced the more sophisticated electronic mass distribution of music under the cover of video clips. Parallel to this, the sellout of the minor and major paraphernalia of the industry, such as signature music instruments, garments, lighters etc., was an additional, indirect form of marketing besides the concerts. In addition, the fierce competition brought about the significant modification of the marketing strategies the music industry had to employ to propel the popular icon to the top of the billboard. The production of stars became a profitable business, and the numerous boards of advisors came up with ever more versatile and marginal behavior-patterns that the star had to act out.